Pelatihan Pembuatan Susu Jagung di Kelompok PKK Desa Rempoah Kecamatan Baturraden - Bivannie Luhsarandini; Hikmah Yuliasari; Vairus Akmala Putri; Hanis Adila Lestari; Hanifah Tsurayya Ayu Wardhani; Dwi Andita; Dean Aria Ghofi (Yayasan Daarul Huda Kruengmane, 2026)
Rempoah Village has abundant corn potential; however, its utilization is still limited to the sale of raw materials or traditional processed products, resulting in suboptimal economic value. In addition, members of the PKK (Family Welfare Empowerment Group) still have limited knowledge and skills in processing local food into innovative, marketable products. This community service activity aims to improve the knowledge and skills of PKK members in processing corn into corn milk as a value-added food product.The implementation method consists of a socialization stage and hands-on training. The socialization stage includes the delivery of materials on the nutritional content of corn, the benefits of corn milk, and principles of sanitation and hygiene. Furthermore, the training stage involves practical sessions on making corn milk, starting from selecting raw materials, processing, to simple packaging. The results show an increase in participants’ knowledge and skills in processing corn into corn milk. Participants were able to produce products with good color, taste, and texture characteristics, and demonstrated high enthusiasm throughout the activity. The impact of this program is an increase in the capacity of PKK members in local food diversification, as well as the emergence of home-based business opportunities that have the potential to increase family income. In addition, this activity encourages the utilization of local resources to support food security. The outputs of this activity include corn milk products, improved participant skills, and the potential establishment of small-scale businesses based on local food. This activity is expected to be sustainable through continued assistance in production and marketing aspects.